The "Eye of the Hurricane" Paradox: An Unexpected and Unequal Rise of Well-Being During the Covid-19 Lockdown in France. (August 2020) - Recchi, Ettore; Ferragina, Emanuele; Helmeid, Emily; Pauly, Stefan; Safi, Mirna; Sauger, Nicolas; Schradie, Jen
Abstract: Panel data covering the French population before and after the outbreak of the Covid-19 epidemic reveal that self-reported health and well-being have improved during the lockdown in comparison to previous years. We name this counterintuitive phenomenon the "eye of the hurricane" paradox: the large majority of individuals who are not infected by the virus may be seeing their current condition in a more positive light than they normally would. There are, however, divergences across social groups that reflect socioeconomic inequalities. In particular, blue-collar workers deviate from the prevailing trend as their level of self-reported health declines over the lockdown period, Parisian residents experience a sudden drop in their subjective well-being, and people working long hours at home exhibit higher levels of stress during the quarantine.